Dental and Oral Health Education: Effective Ways to Prevent Dental and Oral Health Problems - Regia Aristiyanto; Sabtanti Harimurti (OJS Universitas Muhammadiyah Gresik, 2023)
According to Riset Kesehatan Dasar (2018), 57.6% of the Indonesian population have dental health problem. Based on age, the population of 5-9 years (67.3%) were the group with the largest dental problems. The lack of knowledge about dental health was one of the factors that may cause dental health problems, for example, about brushing teeth properly, the percentage was only 2.8%. Based on those data, it was necessary to carry out activities of education about dental health in childhood. Dental health education has been carried out for elementary school students in Srigading Village, Sanden, Bantul, Yogyakarta. The committee was KKN UMY students for the odd semester period 2021/2022. The speaker was a UMY dentistry lecturer who explained dental and oral health, especially related to efforts to prevent dental and oral health problems. Based on the evaluation before and after the implementation of education, it was found that there was an increase in understanding of dental and oral health which was marked by an increase in test scores. An increased understanding of dental and oral health was expected to improve the quality of dental and oral health in childhood.